Dampak Pembangunan Jalan Tol Trans Jawa terhadap Perekonomian Daerah Kabupaten/Kota - Wijaya, Indra; Yudhistira, Muhammad Halley (Jurnal Kebijakan Ekonomi, 2020)
Infrastructure development is one of the driving wheels of economic that have potential to drive increased production, create jobs and reduce the number of poor people. One of the government's focus on infrastructure is the construction of the Trans Java Toll Road that connects the entire Java Island from Jakarta to Surabaya. The purpose of this research is to analyze the impact of the operation of the Trans Java Toll Road which began in part since 2015, 2017, 2018 and 2019 on the Regency/Municipality economy, especially those passed by toll roads. The indicators of regional economy in this research are GRDP per capita, open unemployment rate, dan poverty rate. The research method used is Difference in Difference (DiD) in the form of Staggered Adoption Design (SAD) using 84 regency/municipality data spread across 6 provinces in Java Island from 2012-2919. Estimation results show that the operation of the Trans Java Toll Road has not yet had a stable impact on increasing GRDP per capita, decreasing unemployment rate and reducing poverty rate. The insignificance of the influence of the Trans Java Toll Road is suspected because the analysis is still conducted in the medium term, where generally the influence of the new toll road is seen in the long term.